THERAPEUTIC OF SKIN AGING WITH CARBON DIOXIDE LASER SKIN RESURFACING AND COMBINATION WITH AIR COOLING - Damayanti, NKA Maya; Ratnayanti, IGA Dewi (E-Jurnal Medika Udayana; vol 2 no 12 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 So far, a lot of people who want their face skin always looks young though age continued to grow. It cannot be denied that aging will occur in everyone although some faster or later occur. Various ways were developed by scientists to fix this issue. Laser Skin Resurfacing (LSR) technique to tighten facial skin is a procedure that is popular among the public and the practice of medicine. CO2 LSR technique is still a gold standard was used. Pain during surgery can be reduced when this technique was combined with air cooling. In addition, the adverse effects of post-operative might be tolerated.   /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: skin aging, Carbon Dioxide Laser Skin Resurfacing, air cooling